(untitled) (European Journal of Marketing and Economics, 2025)
In 2012, Croatian Office for Gender Equality published report on position of pregnant workers and working mothers on the national labour market. Survey results clearly demonstrated concerning situation in the labour market where every second pregnant woman was dismissed due to pregnancy. The remaining 50% of pregnant workers and working mothers faced denial of one or more labour rights due to pregnancy or childcare. Apart from violation of basic human rights in the labour market, pregnant workers and working mothers faced discriminatory practices in financial sector i.e. denial of right to take bank loans. These practices are contrary to current Croatian labour and gender equality legislation, as well as European and international legal standards related to protection of pregnant workers and working mothers. Nonethless, due to high national unemployment rate, women faced with labour discrimination rarely use available legal remedies. This paper analysis legal framework applicable to labour discrimination of pregnant workers and working mothers, primarily through the lens of applicable European acquis communautaire i.e. Directives. It also investigates case law of Croatian courts and the European Court of Justice related to labour discrimination of pregnant workers and working mothers. More specifically, research explores convergences and divergences of national and European case law. The aim of the paper is to contribute to academic discussions on the labour market gender equality and measures necessary to achieve full respect of all national and international legal standards.